The Predictability and profitability of Trading Range Break-out Trading Rules: Evidence from Pakistan Stock Exchange - Syed Arshad Ali Shah; Dr.Anwarul Mujahid Shah; Dr.Saiful Mujahid shah (Journal of Business & Tourism, 2021)
The efficient market hypothesis has been one of themost extensively researched topics in the academic literature for decades. An implication ofweak form of efficiency is that the technical trading rules will not produce abnormal returns. The purpose of this research is to analyze findings of application of trading range breakout test on daily closing share prices of 100 companies listed on a Pakistan Stock Exchange over ten years from 2006 to 2015,thus examining its efficiency at the weak form. The results show strong support for trading range break-out rules having both predictability and profitability for PSX. It refers that the returns from these rules are not same as investors earn from a naïve buy and hold strategy. The uses of the trading range break-out rules produce abnormal returns to investors and hence nullify the weak form of efficiency on PSX.